Inequality, Economic Growth, and Technological Change New Aspects in an Old Debate - Grossmann, Volker (Contributions to Economics, 2001)
The book examines the relationship between inequality, growth and technological progress. It provides a broad overview of the existing literature and introduces specific, innovative aspects about the impact of inequality and redistribution on growth when growth is driven by human or physical capital investments, as well as the impact of technological progress and accumulation on the distribution of earnings. There is a special focus on the role of social comparison, redistributive taxation and new information technologies for the relationship between inequality and growth. The analytical part of the book mainly consists of endogenous growth models